ANALISIS FAKTOR-FAKTOR FUNDAMENTAL DAN RESIKO SISTEMATIK TERHADAP HARGA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-218 - Vivin Enidiawati; Rony Malavia Mardani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this study is to determine the influence of fundamental and systematic factors affecting share prices in property companies listed on the Indonesia Stock Exchange (IDX).The population of this study consists of companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The sample used is a company that meets the criteria in the research subject from 2016 to 2018. The analysis method used is the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, hypothesis testing.The results showed that net profit margin, liquidity ratio, debt to equity ratio, price income ratio, and beta had a positive and insignificant effect on stock prices, while price on book value and earnings per share had a positive and significant effect on stock prices.Keywords: Net profit margin, liquidity ratio, debt to equity ratio, price earnings ratio, price to book value and earnings per share, beta and stock price.